Information Management Disipline and Its Implementations - Remzi Salihoğlu (Türk Kütüphaneciliği)
(Samples with Public Enterprises. This upcoming book, including 10 studies from 16 authors approaching the concept of information in epistemologic and the concept of information management in organizational terms, is composed of three chapters including the first one handling knowledge management as power in the new economy, the second one on the public perception of the information, and its role within the economic model of information in competition among SMEs, and the third one on the institutional practices.